(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
Massive intestinal ischemia is one of the most lethal but less frequent abdominal urgencies of hospital admissions, approximately 1 per 1000 admissions according to the American asthmus of gastroenterology. Mortality is 70 to 90%, difficult to diagnose and almost useless treatment when it is late. In cases of massive intestinal resection, ie more than 70% (two thirds), it is associated with high mortality due to dehydration, loss of proteins and minerals, requiring total parenteral nutrition that allows us to improve quality and life expectancy. Home-based parenteral nutrition is a therapeutic alternative for living and integrating into social and working life. The objective of this work is to present a survival alternative to a pathology of difficult diagnosis, poor prognosis and fatal, intestinal ischemia, using home parenteral nutrition. In this experimental study three patients were considered to suffer from this pathology, with massive intestinal resection, performing short anastomosis and placement of central venous device (implantofix) for hydration and early nutrition, with positive results, being a therapeutic alternative, improving quality of life of these patients and incorporated into their homes and their daily tasks.